1979
DOI: 10.1159/000272425
|View full text |Cite
|
Sign up to set email alerts
|

From Social Interaction to Higher Psychological Processes A Clarification and Application of Vygotsky’s Theory

Abstract: Vygotsky’s notions of speech, language and thought have recently begun to receive more attention in the west, but some of his basic distinctions are not well understood. The first part of this paper deals with some of the confusions that have arisen due to inaccurate translation and misunderstanding of Vygotsky’s general theoretical framework. The focus of this analysis is on Vygotsky’s distinction between language and speech. The second part of the paper deals with the emergence of self-regulative capacities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
246
0
37

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(291 citation statements)
references
References 3 publications
8
246
0
37
Order By: Relevance
“…As previously rnentioned, Wertsch (1979) observed that when children are engaged in problem-solving, the y vlill often conduct dialogues with thernselves, posing and responding ta questions, seerningly in 21 an effort to guide their actions, until they have rnastered the task at hand. Wood and Wood (1983) found that different conversational styles of teachers significantly influenced children 1 s patterns of responding and initiative-taking:…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…As previously rnentioned, Wertsch (1979) observed that when children are engaged in problem-solving, the y vlill often conduct dialogues with thernselves, posing and responding ta questions, seerningly in 21 an effort to guide their actions, until they have rnastered the task at hand. Wood and Wood (1983) found that different conversational styles of teachers significantly influenced children 1 s patterns of responding and initiative-taking:…”
Section: Introductionmentioning
confidence: 85%
“…This is an important contrast to many other developmental theories which consider the child to be a self-enclosed unit of analysis and have not regarded interactive processes as an inherent part of the developmental process (Hickmann, 1985 (1962) believed that "it does not simply atrophy but 'goes underground,' i. e., turns into inner speech" (p. 18). Wertsch (1979) proposes four levels in the transition from egocentric to inner speech, or from other-regulation to self-regulation, which, though not exhaustive, do define several points in the developmental path through which the child must pass in order to attain independent problem-solving abilities with regard to a particular task.…”
Section: Introductionmentioning
confidence: 99%
“…e . , developmental) explanation-counterposed to a mechanistic explanation-of psychological functions that 'are organized in accordance with the mediated structure of human activity ' (Cole 1988:140), and scrutinization of the role of situated social practices and interactions on in-time and over-time emergence of higher mental functions (Wertsch 1979). In accord with this stand, Zaretskii (2009) Having defined ZPD as 'the distance between the actual developmental level as determined by independent problem solving and the level of potential development as determined through problem solving under adult guidance or in collaboration with more capable peers' (p. 86), Vygotsky (1978) maintains that ZPD characterizes the maturing mental developmental dynamics and helical trajectory prospectively.…”
Section: Zone Of Proximal Development As a Dynamically Emergent Systemmentioning
confidence: 99%
“…It has been suggested that the development of metacognitive skills may be facilitated by social interactions with others (e.g., teachers, parents, peers, etc.) (e.g., Brown & French, 1979;Brown & Reeve, in press;Flavell, 1979;LCHC, 1983; Metacognition Reconsidered 11 Palinscar & Brown, 1981;Wertsch, 1979). Indeed, theorists of cognitive development from different cultures have long believed that individual thought processes may have their genesis in social interactions (cf.…”
Section: Origins and Growth Of Metacognitionmentioning
confidence: 99%
“…Wertsch (1979) idea of the transition from conscious other-regulation to conscious self-regulation, the complexity of the transition needs to be recognised.…”
Section: Origins and Growth Of Metacognitionmentioning
confidence: 99%